Estudo da coagulação de cultura mista utilizada na biodegradação de efluente de terminais de combustíveis - Vieira, Rafael Bruno (2009)
The present work evaluated the capacity of the utilization of isolated coagulants or in combination with a anionic polyelectrolyte, that made the paper of auxiliante in sedimentation of the mixed cultures (C1) used in biodegradation of hydrocarbons presents in contaminated effluent for diesel oil and gasoline. The coagulants utilized were aluminum sulphate and ferric chloride and the auxiliante the anionic polyelectrolyte. In preliminary tests, accomplished in jar test equipment, concentrations were used of 50, 100, 150, 200, 300, 400, 600, 800, 1000 mg/L for determination of strip that showed the best result of sludge volumetric index (SVI) and the specific oxygen uptake rate (SOUR). The concentrations that showed the best results ranged form 100 to 300 mg/L of ferric chloride and for comparison effect were used the same strip for the aluminum sulphate. After the preliminary tests, was made a central composite design (CCD) with two variables: coagulants concentration (ferric chloride and aluminum sulphate) and polyelectrolyte concentration (anionic polyacrylamide). The concentrations of coagulants used ranged from 85,3 to 314,7 mg/L and concentrations of polyacrylamide ranging from 0 to 3,2. For the CCD with ferric chloride as coagulant the best result of IVL and SOUR were 100,2± 1,0 mL/g and 58,3±1,2 mgO2/g.h, respectively, at a concentration of 200 mg/L ferric chloride and 1,3 mg/L of anionic polyacrylamide. With the aluminum sulphate as coagulnat and with the assistance of polyelectrolyte were good results from SOUR, however, the results of IVL were not satisfactory. We used a sequential batch reactor (SBR) system, which examined the behavior of the mixed culture C1 for the addition of coagulant/auxiliante for several successive cycles verifying the removal of TPH, SSV and SOUR. In 5 cycles in the sequential batch reactor, we observed an increase in the removal of TPH of 75 ± 1.0% to 79 ± 0.5% and the volatile suspended solids increased from 1300 mg/L to 2500 mg/L and had a reduction of SOUR ranging from 58.9 ± 1.0% to 50.5 ± 2.0% in that period. Regarding the kinetics the highest rates of TPH removal and cell growth occur until the third day of proceedings, showing that the degradation of hydrocarbons occurred predominantly by the action microbiologic.The increase of the biodegradation of 83.3 ±1,3 % (seventh day) to 93.5 ± 1.4% ( twenty-fifth day), was high, showing not to be viable to increase the time to improve the process of biodegradation. The behavior shown in the study of the kinetics of TPH removal, volatile suspended solids and specific rate of oxygen consumption, showed that for the biodegradation of gasoline and diesel fuel using a mixed culture C1, in the process with intermittent aeration, microbial activity was related with the growth of biomass and the removal of hydrocarbons.